A Family of Juvenile Idiopathic Arthritis: Case Report - Muaz, Syed Shafi Ahmed; Shamim, Shamim Ahmed; Ahmed, Salim; Siddika, Musammath Moriom; Deb, Bishwajit (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v34i1.5701 Bangladesh Journal of Child Health 2010; Vol.34(1): 31-33